Pengaruh Teknologi dan Diversifikasi Produk Terhadap Pemasaran Stik Gadung Ngalit Kelompok Wanita Tani Saling Asih di Desa Beru Kabupaten Sumabawa Barat - S, Sumarlin; L, Latipa (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to know the influence of technology and product diversification on the marketing of gadung ngalit sticks of Mutual Compassion Women Farmers Group in Desa Beru Jereweh District, West Sumbawa Regency. This type of research is descriptive research with a quantitative approach . The population on this study was all producers and consumers who had ever purchased wheat sticks. The sample in this study was producers and consumers of crushed wheat sticks numbering 50.. The sample was taken by incidental sampling technique. The data collection methods used in the study were interviews (interviews), observations, questionnaires (questionnaires), and documentation. The collected data were analyzed using multiple linear regression analysis technique. The results of this study show that the variable of technology (X1) t-count 2.928 t-table i.e. 2.01063 with its significance value of 0.005 0.05. Which means H0 is rejected and H1 is accepted. This indicates that the technological variable (X1) positively and significantly influences the marketing of barley wheat sticks. Product diversification variable (X2) t-count 4.316 t-table i.e. 2.01063 with its significance value of 0.001 0.05. It means H0 is rejected and H1 is accepted. This indicates that the variable of product diversification positively and significantly affects the marketing of barley wheat sticks. Based on the simultaneous test results, the influence of technology and product diversification on the marketing of wheat sticks is 0.001 0.05 and the F-value calculates 29.949 3.195 which means that H0 is rejected and H1 is accepted, in other words there is a positive and significant influence of the product variable among the variables. barley stick.